Class II Alloantibody and Mortality in Simultaneous Liver‐Kidney Transplantation. Issue 4 (22nd February 2013) - O'Leary, J. G.; Gebel, H. M.; Ruiz, R.; Bray, R. A.; Marr, J. D.; Zhou, X. J.; Shiller, S. M.; Susskind, B. M.; Kirk, A. D.; Klintmalm, G. B.
<x xml:space="preserve">Abstract</x> Hyperacute kidney rejection is unusual in crossmatch positive recipients of simultaneous liver–kidney transplants (SLKT). However, recent data suggest that these patients remain at risk for antibody‐mediated kidney rejection. To further investigate the risk associated with donor‐specific alloantibodies (DSA) in SLKT, we studied 86 consecutive SLKT patients with an available pre‐SLKT serum sample. Serum samples were analyzed in a blinded fashion for HLA DSA using single antigen beads (median florescence intensity ≥ 2, 000 = positive). Post‐SLKT samples were analyzed when available (76%). Thirty patients had preformed DSA, and nine developed de novo DSA. Preformed class I DSA did not change the risk of rejection, patient or allograft survival. In contrast, preformed class II DSA was associated with a markedly increased risk of renal antibody mediated rejection (AMR) (p = 0.006), liver allograft rejection (p = 0.002), patient death (p = 0.02), liver allograft loss (p = 0.02) and renal allograft loss (p = 0.045). Multivariable modeling showed class II DSA (preformed or de novo) to be an independent predictor of patient death (HR = 2.2; p = 0.043) and liver allograft loss (HR = 2.2; p = 0.044). These data warrant reconsideration of the approach to DSA in SLKT.